Management of blast disease of finger millet (Eleusine coracana L. Gaertn) caused by Pyricularia grisea under field conditions in Dolakha, Nepal - Gurung, Suk Bahadur; Dhami, Narayan Bahadur; Subedi, Subash; Shrestha, Jiban (Journal of Agriculture and Natural Resources, 2022)
Lack of understanding regarding the choice of chemical fungicides or botanicals with their optimal doze and spraying schedule is one of the major problems concerning mid-hill farmers to control finger millet diseases in Nepal. In order to assess the effectiveness of the four fungicides, namely Bavistin 50 WP (Carbendazim 50%), SAAF (Carbendazim 12% + Mancozeb 63% WP), RIDOMIL-MZ 72 WP (Metalyxl 8% + Mancozeb 64% WP), BAAN 75 WP (Tricyclazole 75%), and two botanicalsermented anaerobically in cattle urine, an artificial epiphytotic field. In the years 2018 and 2019, the experiment was run using a randomized complete block design with three replications. Carbendazim, one of the chosen treatments, had the greatest impact in lowering the AUDPC values for leaf blast (1818, 1191) as well as neck (4,53) and finger blast (10,45) incidence percentage in both 2018 and 2019 years. Tricyclazole, SAAF, RIDOMIL-MZ, and Lantana camara fermented in cow urine were also discovered to be beneficial throughout the year. So it is recommended to deploy fungicides in a controlled manner through rotation and mixed applications, which is advantageous for both grain and seed production even for minor and underutilized crops from an economic aspect.